Beyond Hawai'i : Native Labor in the Pacific World - Rosenthal, Gregory Samantha, 1983- (Book collections on Project MUSE., 2018)
"In the century from the death of Captain James Cook in 1779 to the rise of the sugar plantations in the 1870s, thousands of Kanaka Maoli (Native Hawaiian) men left Hawai'i to work on ships at sea and in na 'aina 'e (foreign lands)--in California, the Arctic Ocean, the equatorial islands, and throughout the Pacific Ocean. Beyond Hawai'i tells the stories of these forgotten indigenous workers and how their labor shaped the Pacific World, the global economy, and the environment. From sandalwood harvesting to whaling, guano harvesting, and gold mining, these migrant workers were essential to the expansion of transnational capitalism and global ecological change. Bridging American, Chinese, and Pacific historiographies, Beyond Hawai'i is the first book to argue that indigenous labor--rather than ships, goods, and diseases--was the glue that held the Pacific World together"--Provided by publisher